Implementing AHP Method for Determining Level Priority of Vendor Selection - Kartika Salsabilla Wulandari; Sri Widaningrum; Sheila Amalia Salma (School of Industrial and System Engineering, Telkom University, 2023)
Vendors are suppliers of goods or services that help the production process of a company. One ofthe companies that carry out vendor selection is CV Milyarda Cipta Karya which is engaged infashion. Vendor selection is an activity to determine vendors who will work with the company tohelp the production process. Based on an assessment of the 30 most popular CV Milyarda CiptaKarya's products on Shopee, there are consumer complaints about the inconsistent quality ofmaterials. This problem is caused by the absence of standards governing the mechanism forselecting fabric vendors. Therefore, it is necessary to know the priority level of vendor selectioncriteria. Vendor selection criteria are Quality of goods, response time, location, flexibility, price,vendor inventory policy, and vendor service. The data needed in the design are vendor selectioncriteria according to William J Stevenson, namely hierarchical data and criteria weightingquestionnaires. The method used to determine the priority level of vendor selection criteria is theAnalytical Hierarchy Process method. Based on the calculation of the AHP method, the resultsobtained are the criteria for quality of goods 0.19, location 0.12, response time 0.12, vendorinventory policy 0.09, flexibility 0.09, price 0.11, and vendor service 0.28. The largest priority valueis vendor service and the smallest is flexibility.